The content analysis of concept mapping studies in education: the status of concept mapping studies in our country in the last 10 years - ŞENGÜL, SARE (My University, 2022)
The concept maps are graphical tools that show and organize relationships between concepts [1]. It is a set of semantic relations that enable information to be concretized and transformed into visuals [2]. It is used for many purposes in terms of revealing many skills such as critical thinking and reflective thinking, emphasizing the relationships between concepts, evaluating the deficiencies and facilitating the production of knowledge [3]. It emerges as rich learning opportunities in learning environments [4]. In this direction, a detailed examination of how concept mapping is used in educational fields, the general characteristics of the studies related to this field, their aims and results will create a holistic evaluation for the studies to be made in this field. In this context, the aim of the research is to analyze the current situation in our country in the last 10 years by analyzing the content of concept mapping studies in education. The theses on concept maps in the field of education completed between 2013-2022 were determined and examined. In this context, first of all, 312 theses were reached, the year limit and the subject of the research were clarified with keywords and 64 theses were examined. Studies that do not focus on concept maps in the summaries of the studies and that they are used only superficially with many methods and techniques are excluded from the scope. According to the research findings; most of the studies consist of the master's theses (f=51). The number of the doctoral theses (f=13) was found to be less than the master's theses examined. Although the published studies vary according to the years, the most studies on concept mapping were reached in 2019 (f=20). The education fields in which the studies were conducted were respectively “science (f=12), mathematics (f=11), Turkish (f=9), biology (f=5), chemistry (f=4), computer and instructional technologies (f=3”. ), geography (f=3), religious education (f=3), preschool (f=3), social studies (f=3), English (f=2), special education (f=2), Arabic teaching (f=1), physical education (f=1), education programs (f=1), Turkish literature (f=1)”. When the concept maps were examined in particular for the mathematics lesson, it was determined that the subjects prepared/applied were mostly "polygons, fractions, rational numbers, exponential numbers". When the general characteristics of the studies are examined; it was determined that the sample group consisted mostly of secondary school students (f=28), and the quasi-experimental design with pre-test-post-test control group (f=31) was mostly preferred as a quantitative research method. The distribution of the studies according to the aims and results is examined in detail and suggestions will be made according to the outputs obtained.
Keywords: Education; concept mapping; content analysis